x平方-(2x平方-xy+y平方)+(-x平方+3xy-2y平方) 其中X=-2 y=3
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/04 01:33:12
x平方-(2x平方-xy+y平方)+(-x平方+3xy-2y平方)其中X=-2y=3x平方-(2x平方-xy+y平方)+(-x平方+3xy-2y平方)其中X=-2y=3x平方-(2x平方-xy+y平方
x平方-(2x平方-xy+y平方)+(-x平方+3xy-2y平方) 其中X=-2 y=3
x平方-(2x平方-xy+y平方)+(-x平方+3xy-2y平方) 其中X=-2 y=3
x平方-(2x平方-xy+y平方)+(-x平方+3xy-2y平方) 其中X=-2 y=3
首先 化简
x^2-(2x^2-xy+y^2)+(-x^2+3xy-2y^2)
=x^2-2x^2+xy-y^2-x^2+3xy-2y^2
=-2x^2+4xy-3y^2
然后在把x=-2,y=3带进去
=-2*(-2)^2+4*(-2)*3-3*3^2
=-8-24-27=-59
计算 (x平方+2xy+y平方)(x平方-xy+y平方)平方
【2x(x平方y-xy平方)+xy(xy(xy-x平方)】除以x平方y
(2xy平方+3xy平方)-(6x平方y-3xy平方)=
(2X平方y+3xy平方)-(6x平方-3XY平方)(计算)
(x平方+2xy+y的平方)/(x+y)
(x平方+xy-y平方)(x平方+xy+y平方)-x平方(x+y)平方 化简
因式分解(x的平方+2xy+y的平方)(x的平方-xy+y的平方)的平方
3x平方-5x平方y-{2x平方y+6xy平方-[2xy平方-3x平方y+(3x平方y-4xy平方】}
(3X平方-5Y)+[-3XY-2(X平方-XY)+Y平方]
x平方(4x平方+4xy+y平方)-4x平方y平方
化简(x平方-y平方)/(x+y)+(x平方-2xy+y平方)/(x-y)
(3x平方-4y平方)+[-(x平方-2xy-y平方)]-[(3x平方-2xy-y平方)]
X平方Y-2XY平方+Y平方 因式分解
3(xy的平方-x的平方y)-2(xy+xy的平方)+3x的平方y
计算:2x(-xy)的平方-x的平方(x的平方y的平方-y的平方)
x平方+y平方+2xy分之x平方-4y平方除以x平方+xy分之2y+x
-2X的平方Y+(-1/2XY的平方)+2X平方Y+(-XY平方)
x平方+3xy+2y平方/x平方y+2xy平方